PENGARUH EVALUATIVE DIMENSIONS OF ADVERTISING TERHADAP BEHAVIORAL INTENTION MELALUI EMOTIONAL RESPONSES DAN PERCEIVED VALUE - Stefanus Irvan (Jurnal Manajemen dan Pemasaran Jasa, 2013)
The purpose of this research was to investigate how the company can win the competition and satisfied customers through the promotional activities that affect the behavioral intention. The design of this research applies a survey in Pizza Hut restaurant the customers for testing the hypothesis. Meanwhile the required data consist of three variables are evaluative dimensions of advertising as independent variable, emotional responses and perceived value as intervening variable. Finally, behavioral intention as dependent variable.The aggregate numbers of customer being respondent of the study are 150 customer. Data analysis used in this research was consists of Structural Equation Modelling by AMOS 6.0 as software. The result of this research conclude that people consider another customer’s failure to be the firm’s responsibility when they perceive that the failure is under the firm’s volitional control (i.e. controllability attribution). This controllability attribution leads to customer expectations of compensation for recovery from dissatisfaction.Keywords : Advertising, Behavioral Intention, Customer Satisfaction, EmotionalResponses, Perceived Value